2022
DOI: 10.3390/rs14041050
|View full text |Cite
|
Sign up to set email alerts
|

Global Spatiotemporal Variability of Integrated Water Vapor Derived from GPS, GOME/SCIAMACHY and ERA-Interim: Annual Cycle, Frequency Distribution and Linear Trends

Abstract: Atmospheric water vapor plays a prominent role in climate change and atmospheric, meteorological, and hydrological processes. Because of its high spatiotemporal variability, precise quantification of water vapor is challenging. This study investigates Integrated Water Vapor (IWV) variability for the period 1995–2010 at 118 globally distributed Global Positioning System (GPS) sites, using additional UV/VIS satellite retrievals by GOME, SCIAMACHY, and GOME-2 (denoted as GOMESCIA below), plus ERA-Interim reanalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Water vapour column density or vertically integrated water vapour (IWV) are monitored by various measuring instruments such as ground-based receivers of the Global Navigation Satellite System (GNSS), radiosondes, microwave radiometers, or Fourier transform infrared (FTIR) spectrometers [2]. Various studies indicated that IWV increased by several percents per decade, and this positive trend of IWV conforms with the expected increase of the water vapour abundance due to the increase of the air temperature as a consequence of man-made global warming [2][3][4][5][6]. According to the Clausius-Clapeyron relationship, a warmer atmosphere is associated with an amplification of the water vapour abundance.…”
Section: Introductionmentioning
confidence: 95%
“…Water vapour column density or vertically integrated water vapour (IWV) are monitored by various measuring instruments such as ground-based receivers of the Global Navigation Satellite System (GNSS), radiosondes, microwave radiometers, or Fourier transform infrared (FTIR) spectrometers [2]. Various studies indicated that IWV increased by several percents per decade, and this positive trend of IWV conforms with the expected increase of the water vapour abundance due to the increase of the air temperature as a consequence of man-made global warming [2][3][4][5][6]. According to the Clausius-Clapeyron relationship, a warmer atmosphere is associated with an amplification of the water vapour abundance.…”
Section: Introductionmentioning
confidence: 95%
“…Currently, methods commonly used to observe PW amounts include radiosonde observations [10], microwave radiometers [11,12], global navigation satellite system (GNSS) [13][14][15], and satellite remote sensing [16][17][18][19]. Of these, radiosonde observations are the traditional observation method [20].…”
Section: Introductionmentioning
confidence: 99%
“…Those papers can be arranged in major groups. Several papers [1][2][3] discuss different aspects in dealing with the estimation of long-term GNSS-derived water vapor trends and intercomparisons with external sources and NWP models. Other papers [4] use GNSS-estimated tropospheric parameters to evaluate NWP models and use these parameters for building ZTD climatological [5][6][7] or precipitation [8,9] models.…”
mentioning
confidence: 99%